2022
DOI: 10.1016/j.jhqr.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of front-line healthcare workers’ Knowledge, Attitude and Practice after several months of COVID-19 pandemic

Abstract: Background: Frontline healthcare workers (F-HCWs) are at the forefront of medical care providers against the novel coronavirus 2019 (COVID-19) pandemic which has life-threatening potentials. Inadequate knowledge and incorrect attitudes among HCWs can directly influence practices and lead to delayed diagnosis, poor infection control practices, and spread of disease. Objectives: The aim of this study was to assess the knowledge, attitude and practice (KAP) regarding the COVID-19 pandemic among the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
3
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 12 publications
7
20
3
5
Order By: Relevance
“…Meanwhile, 12.2 % choose neutral impact on others. The finding of this present study is in line with the result of another research conducted in India (Maurya et al, 2020).…”
Section: Attitude Towards Handling Covid-19 Among Nurses In Ummcsupporting
confidence: 92%
See 1 more Smart Citation
“…Meanwhile, 12.2 % choose neutral impact on others. The finding of this present study is in line with the result of another research conducted in India (Maurya et al, 2020).…”
Section: Attitude Towards Handling Covid-19 Among Nurses In Ummcsupporting
confidence: 92%
“…According to Maurya et al (2020), respondents in the nursing profession have the highest level of knowledge compared to other healthcare workers. However, Salman et al (2020) found that 75.5% of respondents had good knowledge of COVID-19, where the doctors were found to have better knowledge scores than the other health professionals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anticipating the spike in cases in near future, the strategy of state government in this direction from beginning was to increase the number of beds like 10,000 beds in level one, 5000 beds in level two, and 2000 beds in level three defined in level of Hospital L1, L2 (with oxygen), and L3 (with ventilator). Various training was imparted to frontline health-care workers and had better overall knowledge, attitude, and practice (KAP) toward COVID-19 compared to any HCWs specially technicians and students ( Maurya et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While there is a growing body of research on aspects of COVID-19 related health literacy of the general population [4,15,16,22] or specific populations, e.g., migrants, children, students, or patients [8][9][10][11]13,[19][20][21]23], little is known about the COVID-19 related health literacy of healthcare professionals, such as physicians, nurses, or psychologists. Since 2020, many studies have investigated the knowledge, attitude, and behavior of healthcare professionals worldwide [24][25][26][27][28][29][30][31][32][33][34]. The results indicate a lack of adequate knowledge about COVID-19 in many cases (6-42%) [24,25,27,32].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals having a higher education were found to have better knowledge about COVID-19 [28,33,35]. Strong significant correlations were found between knowledge, attitude, and behavior [26,34]. However, data on the COVID-19 related health literacy that allow the analysis of healthcare professionals' knowledge, motivation, and ability to find, understand, evaluate, and use the information on COVID-19 is still missing.…”
Section: Introductionmentioning
confidence: 99%